2018
DOI: 10.18295/squmj.2018.18.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Early Pregnancy Obesity on Maternal, Fetal and Neonatal Health: Retrospective cohort study from Oman

Abstract: abstract:Objectives: This study aimed to determine the prevalence of early pregnancy obesity among Omani women and to review maternal antenatal complications, intrapartum and postpartum events and neonatal complications among such women in comparison to women of normal weight. Methods: This retrospective cohort study included 2,652 pregnant Omani women who delivered at the Royal Hospital, Muscat, Oman, between November 2011 and April 2012. The patients' electronic medical records were reviewed for antenatal, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…The size of the cohorts ranged from 23 pregnant women with a known diagnosis of idiopathic thrombocytopenic in Saudi Arabia [62] to 158,006 delivering mothers in Kuwait [81]. Majority (64.2%) of the cohort studies were in Saudi Arabia [25][26][27]40 [54,55,78,[102][103][104], and one (1.2%) in Bahrain [22] (see Additional file 3: Table S2).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The size of the cohorts ranged from 23 pregnant women with a known diagnosis of idiopathic thrombocytopenic in Saudi Arabia [62] to 158,006 delivering mothers in Kuwait [81]. Majority (64.2%) of the cohort studies were in Saudi Arabia [25][26][27]40 [54,55,78,[102][103][104], and one (1.2%) in Bahrain [22] (see Additional file 3: Table S2).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Thirty-four cohort studies (42.0%) were identified as a prospective design (19 in [81], and three in the UAE). Fiftytwo (64.2%) cohort studies enrolled pregnant mothers at varying stages of their pregnancy with different characteristics such as diabetic and non-diabetic mothers [26,67], obesity [42,47,54], singleton [41,48,99] or triplet pregnancies [91], teenage women [112], multipara women [82,86,98], and women with systemic lupus erythematosus (SLE) [27]. Eight studies (9.9%) enrolled pregnant mothers at varying stages after delivery [24,49,58,59,81,84,88,99].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…30.0 kg/m2, is increasing over time. 5,12,18 Pregestational BMI is a risk factor for the development of maternal and perinatal complications. 24,27 In the clinical practice, obesity and gestational diabetes commonly coexist and it is controversial which one the two conditions (gestational diabetes or maternal obesity) is more strongly associated with risk for adverse maternal and neonatal outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported on the association between higher body mass index (BMI) and increased risk of adverse maternal outcomes and obstetric intrapartum complications . These complications include hypertensive disorders in pregnancy such as eclampsia/preeclampsia, gestational diabetes mellitus (GDM), thromboembolic disorders, postpartum haemorrhage (PPH), and maternal deaths as well as services indicative of complications include induction of labour and caesarean delivery . In addition, the evidence from 14 countries in SSA shows that obesity in pregnancy is associated with increased risks of adverse labour, child, and maternal outcomes …”
Section: Introductionmentioning
confidence: 99%